The role of debridement in wound bed preparation in chronic wound: A narrative review - Deena Clare Thomas; Chong, Li Tsu; Rose A. Nain; Norkiah Arsat; Soong, Shui Fun; Nik Amin Sahid Nik Lah (Elsevier Ltd, 2021)
Objective: To provide an overview of the types of wound debridement and update the available scientific consensus on the effect of wound debridement. Methods: The articles were searched through CINAHL, PubMed, Cochrane Library, and Medline database for relevant articles on all types of wound debridement. Articles included were all systematic review on the effectiveness of wound debridement-related outcome, published within the year 2017 until Aug 2021, in English. Results: A total of seven scientific articles had been selected for review out of 318 screened. The authors reviewed a total of 318 titles and abstracts related to wound debridement effectiveness. Seven articles that were selected were narratively reviewed by two authors. The findings of the review were organized into autolytic, enzymatic, sharp, surgical, biological, and mechanical debridement methods and includes the advantages and disadvantages of each. The author further explored on the role of wound debridement according to wound bed preparation model. Articles were synthesized and organized based on the authors, year, total studies included in the systematic review, study range of year, total sample, debridement method, wound types, and findings. Conclusion: Maggot debridement therapy showed a consistent finding in terms of effectiveness in debriding chronic wounds. The newer debridement method includes hydro-surgery, low-frequency ultrasonic and enzymatic collagenase debridement were getting more attention due to faster wound bed preparation and less painful. However, these newer method of debridement’s showed inconclusive findings and the patient safety was not clearly defined. A higher level of review is warranted in the future study.